Early neonatal morbidities and neurological functioning of preterm infants 2 weeks after birth. (November 2018) - Hempenius, Maaike; Verhagen, Elise; Tanis, Jozien; Einspieler, Christa; Bos, Arend
Abstract Objective To determine the association between potential neonatal risk factors and the quality of general movements (GMs) in preterm infants. Study design Prospective cohort study in 67 preterm infants. From video recordings made on Days 8 and 15, we scored the GMs as normal/abnormal and detailed aspects using the general movement optimality score (GMOS). Risk factors included respiratory insufficiency requiring mechanical ventilation, patent ductus arteriosus (PDA), and abnormal blood glucose levels. We used multiple regression analyses. Result On Day 8 after birth, the presence of a PDA remained in the multivariable model, explaining 17.1% of the variance in GMOS (beta, −0.414). On Day 15, duration of mechanical ventilation and frequency of hypoglycemic episodes explained 38.8% of the variance (betas, −0.382 and −0.466, respectively). Conclusion In preterm infants, PDA, duration of mechanical ventilation, and frequency of hypoglycemic episodes were associated with poorer neurological functioning during the first 2 weeks after birth.